(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aim to determine the relationship between perceived social support, psychological resilience and happiness levels of hemodialysis patients.Material and Methods: A total of 120 patients who applied to the Gaziantep Research and Training Hospital during the dates of September-October 2018 for hemodialysis treatment due to chronic renal failure were included in this cross sectional study. “Sociodemographic questionnaire”, “Multidimensional Scale of Perceived Social Support (MSPSS)”, “Oxford Happiness Questionnaire (OHQ)” and “Resilience Scale for Adults (RSA)” were used for assessment. Statistical analyses were made using IBM SPSS (Statistics for Windows, Version 21.0, Armonk, NY, IBM Corp).Results: Total score means for patients were determined as; OHQ 96.87 ± 21.35, RSA, 97.58 ± 22.73, MSPSS 50.88 ±20.98. There was a positive correlation between OHQ total score and RSA total score (r: 0.59 p 0.05) and positively with MSPSS total score (r: 0.58 p 0.05). There was a positive correlation between RSA and MSPSS total scores (r: 0.55. P 0.05). Conclusion: As perceived social support increases in hemodialysis patients, happiness levels and psychological resilience increase. Also happiness levels increase with increasing psychological resilience. Increasing the social support systems of hemodialysis patients can increase their happiness levels and psychological resilience.